THE INFLUENCE OF WORK DISCIPLINE AND SITUATIONAL LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT PT SMO IN BATAM - Atmaja, Agus Sekti Susila; Sumarya, Edi; Nuraeni, Brigida Endah (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
This research is entitled